Industrial application of PV/T solar energy systems - Tripanagnostopoulos, Yiannis; Kalogirou, Soteris A.; Tripanagnostopoulos, Yiannis (My University, 2007)
Hybrid photovoltaic/thermal (PV/T) systems consist of PV modules and heat extraction units mounted together. These systems can simultaneously provide electrical and thermal energy, thus achieving a higher energy conversion rate of the absorbed solar radiation than plain photovoltaics. Industries show high demand of energy for both heat and electricity and the hybrid PV/T systems could be used in order to meet this requirement. In this paper the application aspects in the industry of PV/T systems with water heat extraction is presented. The systems are analyzed with TRNSYS program for three locations Nicosia, Athens and Madison that are located at different latitudes. The system comprises 300 m2 of hybrid PV/T collectors producing both electricity and thermal energy and a 10 m3 water storage tank. The work includes the study of an industrial process heat system operated at two load supply temperatures of 60 °C and 80 °C. The results show that the electrical production of the system, employing polycrystalline solar cells, is more than the amorphous ones but the solar thermal contribution is slightly lower. A non-hybrid PV system produces about 25% more electrical energy but the present system covers also, depending on the location, a large percentage of the thermal energy requirement of the industry considered. The economic viability of the systems is proven, as positive life cycle savings are obtained in the case of hybrid systems and the savings are increased for higher load temperature applications. Additionally, although amorphous silicon panels are much less efficient than the polycrystalline ones, better economic figures are obtained due to their lower initial cost, i.e., they have better cost/benefit ratio.
Keywords: Photovoltaics; Hybrid PV/T systems; Industrial process heat